2010
DOI: 10.2310/6670.2010.00030
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Thyroid Artery Pseudoaneurysm Caused By Blunt Trauma

Abstract: Injury to the inferior thyroid artery (ITA) is an extremely rare complication of blunt neck trauma. The subtle initial clinical presentation and the potential life-threatening sequelae make it a diagnostic and therapeutic challenge. We report a case of an ITA pseudoaneurysm caused by seat-belt injury. Imaging findings and successful treatment with coil embolization are described. The role of noninvasive imaging techniques in establishing the diagnosis is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[8][9][10][11] Other causes such as stellate ganglion blocks, central venous catheter placement, [11] and direct trauma may lead to serious injury to ITA. [12] It is reported that using imaging techniques such as ultrasound to identify any variations in anatomical structures prior to surgical and interventional procedures also prevents damage to ITA. [11] 172 Özen KE et al Variations of superior thyroid artery and ITA have been previously published by many authors.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Other causes such as stellate ganglion blocks, central venous catheter placement, [11] and direct trauma may lead to serious injury to ITA. [12] It is reported that using imaging techniques such as ultrasound to identify any variations in anatomical structures prior to surgical and interventional procedures also prevents damage to ITA. [11] 172 Özen KE et al Variations of superior thyroid artery and ITA have been previously published by many authors.…”
Section: Discussionmentioning
confidence: 99%
“…There were 8 (57.1%) women and 6 (42.9%) men varying in age from 50 (6,7,9). Other four cases developing pseudoaneurysm underwent coil embolization and resolved (8,(10)(11)(12).…”
Section: Case Presentationmentioning
confidence: 99%
“…We conducted a systematic review searching database PubMed, Embase and Web of Science from inception to April 2019. The base characteristics of the 14 included cases from 7 articles were shown in Table 1 (6)(7)(8)(9)(10)(11)(12). There were 8 (57.1%) women and 6 (42.9%) men varying in age from 50 (6,7,9).…”
Section: Case Presentationmentioning
confidence: 99%
“…Diagnosis of inferior thyroid artery abnormalities can be made by Color Doppler US, computed tomography angiography (CTA) or conventional angiography (3)(4). In general, gray-scale US in combination with color or power Doppler is noninvasive, safe, fast, cost-effective and feasible technique for neck imaging, especially valuable for differential diagnosis, because ITA thrombosis would show a connection to arterial system.…”
Section: Case Reportmentioning
confidence: 99%